Manajemen Tata Laksana Penyakit Paru Obstruktif Kronik: Literature Review - Putri Irwanti Sari; Keshy Maghfirah (STIKES Garuda Putih, 2024)
Chronic Obstructive Pulmonary Disease (COPD) is a significant global health issue. It is characterized by chronic and progressive narrowing of the airways, resulting in symptoms such as shortness of breath, cough, and excessive mucus production. Major risk factors include smoking, air pollution, hazardous chemicals, and genetic factors. The impact of COPD on the quality of life and healthcare costs is substantial. In 2015, the World Health Organization (WHO) reported that around 65 million individuals suffer from COPD. In Indonesia, the prevalence of COPD is 3.7%, with significant regional variations. This study is a literature review that summarizes and critically analyzes existing literature, theories, research findings, and reference materials from various sources. Various approaches to managing COPD include physical therapy, breathing exercises, pharmacological therapy, and self-care programs. Physical therapy involves chest physiotherapy, which includes postural drainage and breathing exercises. Breathing exercises using the Pursed Lips Breathing (PLB) technique have also been proven effective. Pharmacological therapy includes bronchodilators and corticosteroids, while nebulizer therapy is used in some cases. Nursing interventions for COPD management involve appropriate positioning, effective cough exercises, and patient education. Self-care programs based on home care are recommended to improve patients' quality of life. To manage COPD symptoms, it is recommended to integrate breathing therapy techniques, foster collaborative healthcare teams, provide patient education, and conduct further research.